Faktor dominan kejadian konstipasi fungsional pada remaja di Jakarta - Felicia Thea; Trini Sudiarti; Kusharisupeni Djokosujono (Jurnal Gizi Klinik Indonesia, 2020)
Dominant factors of functional constipation among adolescent in JakartaBackground: The impact of functional constipation, including the quality of life decreases, increase the additional health costs that must be incurred, and reduce productivity. Previous research in various places in Indonesia shows that functional constipation is experienced among adolescents, percentages between 24.6-68.5%.Objective: Determine the relationship and dominant factor between gender, fiber intake, fluids intake, consumption of probiotic drinks, physical activity, nutritional status, stress, and nutritional knowledge on the incidence of functional constipation.Methods: The study design was cross-sectional. The number of respondents studied was 150 high-school students from class X and XI. The sample selected by using a total sampling system. Data collected using the Roma III questionnaire of functional constipation, physical activity using the Physical Activity Questionnaire for Adolescent, and stress level using the Holmes and Rahe Stress Scale for students.  Nutritional knowledge was obtained by filling out a questionnaire. Food recall 2x24 hours to assess fiber intake, fluid, and probiotic drinks. Measure body weight and height of students to determine nutritional status. Data analyzed using univariate, Chi-Square test for bivariate, and multiple logistic regression tests for multivariate.Results: 75.3% of students had functional constipation, 64.0% less fiber intake,54.0% less fluid intake, 91.3% less physical activity, 62.0% did not consume probiotic drinks, 38.7% were obese and 30.0% lacking in nutrition knowledge. Dominant factor of functional constipation was physical activity (p-value 0.035; OR 3.57; CI 1.09-11.66).Conclusions: Low physical activity can increase the incidence of functional constipation in adolescents at Jakarta.